Healing traumatic memories in psychosis: a response to Sin and Spain (2016). Issue 1 (2nd January 2017) - Hardy, Amy; van den Berg, David
Abstract: We question the conclusions of Sin and Spain's meta-analysis of therapy for post-traumatic stress disorder in psychosis and tentatively suggest direct trauma memory exposure is delivered, without adaptation, when people consent (Sin, J., & Spain, D. (2016). Psychological interventions for trauma in individuals who have psychosis: A systematic review and meta-analysis. Psychosis . 1–15. doi:10.1080/17522439.2016.1167946 .